NIAT BELI MASYARAKAT TERHADAP DISTRO LABEL CLOTHING DI SURAKARTA - Titin Hargyatni; Diani Putri Utami (MANAJEMEN, 2021)
This study aims to determine the purchase intention of private label clothing in Surakarta which has a relationship from the effect of risk, product quality, relative price and value in Rown Division distributions. The sample in this study were 100 respondents who bought Rown Division's products. This study uses a non-probability sampling technique with a purposive sampling approach, namely a sampling technique with certain criteria. The data analysis method used is multiple linear regression including t test, F test, coefficient of determination. The results showed that the variables of product value, relative price, product quality and risk had a positive and significant effect on people's buying intentions for clothing products. The magnitude of the coefficient of determination (R2) obtained a value of 60.9%, which means that the variables of product value, relative price, product quality and ris in this study were able to build purchase intentions of 60.9%, while the remaining 39.1% was explained by other factors outside from this research